A Survey on Global Software Development: Current Practices and Challenges - Herculani, Júlio Budiski; Amaral, Aline M. M. Miotto; Colanzi, Thelma Elita (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Global Software Development (GSD) is a growing reality in the software organizations, aiming to meet the needs for agility and competitiveness in the globalized market. GSD has been propelled during the COVID-19 pandemic, reaching new heights. Problem: One of the critical challenges in GSD is how the geographical distribution of development teams impacts people communication and collaboration, which can lead to inefficiencies in the information system projects. Proposed Solution: This study explores and summarizes the current practices and challenges in GSD by gathering the perceptions and experiences of Brazilian developers through a comprehensive survey. IS Theory: The research is grounded in the theory of socio-technical systems, particularly focusing on the interplay between organizational structures and the technologies that support distributed software teams. Method: A total of 44 Brazilian software developers answered the survey, providing valuable insights into their perceptions and experiences. The study provides a detailed overview of the complexities and opportunities inherent in GSD. Summary of Results: The findings emphasize the critical importance of effective communication in managing distributed teams and highlight challenges in remote collaboration, such as the need for robust digital infrastructure and enhanced information security. The main contribution of this work encompasses socio-technical issues regarding GSD, which emerged or remain after the COVID-19 pandemic, and that can be addressed by software organizations.